Revival of Bulgarian Folk Music During Socialism and the Post-Socialist Transition: Music and Cultural Identity - Kirilov, Kalin S. (MUSICultures, 2010)
This article juxtaposes two periods of Bulgarian folk music revival, which were separated by a period of rejection of Bulgarian traditions and cultural values, and problematizes the success of chalga, a pan-Balkan musical phenomenon from the post-socialist period. By engaging current research of American and Bulgarian scholars and reflecting on the author’s recent fieldwork and personal experiences as a performer of Bulgarian folk music, this study raises questions regarding the relationships between state-imposed nationalism and folk traditions, village culture and modern life, the role of media in the dissemination of musical traditions, and the importance of folk music in the construction of modern Bulgarian cultural identity.